Spray-coated paper supercapacitors - Mehmet Girayhan Say (Nature Portfolio, 2020)
Abstract The increasing demands to further electrify and digitalize our society set demands for a green electrical energy storage technology that can be scaled between very small, and heavily distributed electrical energy sources, to very large volumes. Such technology must be compatible with fast-throughput, large-volume and low-cost fabrication processes, such as using printing and coating techniques. Here, we demonstrate a sequential production protocol to fabricate supercapacitors including electrodes based on cellulose nanofibrils (CNF) and the conducting polymer PEDOT:PSS. Thin and lightweight paper electrodes, carbon adhesion layers and the gel electrolyte are fabricated using spray coating, screen printing, and bar coating, respectively. These all solid-state supercapacitors are flexible, mechanically robust and exhibit a low equivalent series resistance (0.22 Ω), thus resulting in a high power density (∼104 W/kg) energy technology. The supercapacitors are combined and connected to a power management circuit to demonstrate a smart packaging application. This work shows that operational and embedded supercapacitors can be manufactured in a manner to allow for the integration with, for instance smart packaging solutions, thus enabling powered, active internet-of-things (IoT) devices in a highly distributed application.